Clinical and laboratory features of seventy-eight UK patients with Good's syndrome (thymoma and hypogammaglobulinaemia). (21st October 2018) - Zaman, M; Huissoon, A; Buckland, M; Patel, S; Alachkar, H; Edgar, J D; Thomas, M; Arumugakani, G; Baxendale, H; Burns, S; Williams, A P; Jolles, S; et al.
Summary: Good's syndrome (thymoma and hypogammaglobulinaemia) is a rare secondary immunodeficiency disease, previously reported in the published literature as mainly individual cases or small case series. We use the national UK-Primary Immune Deficiency (UKPID) registry to identify a large cohort of patients in the UK with this PID to review its clinical course, natural history and prognosis. Clinical information, laboratory data, treatment and outcome were collated and analysed. Seventy-eight patients with a median age of 64 years, 59% of whom were female, were reviewed. Median age of presentation was 54 years. Absolute B cell numbers and serum immunoglobulins were very low in all patients and all received immunoglobulin replacement therapy. All patients had undergone thymectomy and nine (12%) had thymic carcinoma (four locally invasive and five had disseminated disease) requiring adjuvant radiotherapy and/or chemotherapy. CD4 T cells were significantly lower in these patients with malignant thymoma. Seventy-four (95%) presented with infections, 35 (45%) had bronchiectasis, seven (9%) chronic sinusitis, but only eight (10%) had serious invasive fungal or viral infections. Patients with AB-type thymomas were more likely to have bronchiectasis. Twenty (26%) suffered from autoimmune diseases (pure red cell aplasia, hypothyroidism, arthritis, myasthenia gravis, systemic lupus erythematosus, Sjögren's syndrome). There was no association between thymoma type and autoimmunity. Seven (9%) patients had died. Good's syndrome is associated with significant morbidity relating to infectious and autoimmune complications. Prospective studies are required to understand why some patients with thymoma develop persistent hypogammaglobulinaemia. Graphical Abstract: